Extending the biocatalytic scope of regiocomplementary flavin-dependent halogenase enzymes1. Issue 6 (18th June 2015) - Shepherd, Sarah A.; Karthikeyan, Chinnan; Latham, Jonathan; Struck, Anna-Winona; Thompson, Mark L.; Menon, Binuraj R. K.; Styles, Matthew Q.; Levy, Colin; Leys, David; Micklefield, Jason
<x xml:space="preserve">Abstract</x> Targeted mutagenesis increases the activity and alters the regioselectivity of flavin-dependent halogenases.